PENGARUH SUPERVISI PENDIDIKAN TERHADAP KINERJA GURU DALAM PEMBELAJARAN DI SEKOLAH DASAR NEGERI 6 PULAU RIMAU KABUPATEN BANYUASIN - Wasiman Wasiman; Sumani Sumani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The low quality of education in Indonesia requires efforts to improve teacher performance as one of the factors that influence teaching efficiency. The importance of the role of teachers in learning, efforts are needed to improve teacher performance through a provision of guidance and also encouragement from the principal. Guidance for principals on teachers regarding learning activities is known as academic supervision. The purpose of this study was to analyze the effect of academic supervision on teacher performance. This research is an ex post facto study. Data processing begins with testing the validity and reliability of research instruments using the Cronbach's Alpha test. Furthermore, the analysis prerequisite test included normality tests and linearity tests. In order for teacher performance to increase, academic supervision must be carried out optimally. Recommendations based on the results of the study include the implementation of academic supervision, principals must pay more attention to aspects of supervision, while in terms of teacher teaching performance, teachers must further improve their performance, especially in aspects of learning evaluation and follow-up of student assessment result.